A real-world evidence study to evaluate the efficacy of software-driven digital therapeutics on major adverse cardiovascular events, vitals, adherence to medication and lifestyle changes among patients with coronary artery disease or post-coronary interventions - Abhijeet Palshikar,; Chetan H. Gharat,; Kamlesh Patel, (International Journal of Research in Medical Sciences, 2023)
Background: Coronary artery disease (CAD), a leading cause of cardiovascular disease (CVD) mortality worldwide, is a major health concern in India due to the high rates of the disease. Acute coronary syndrome (ACS) is a prevalent form of CAD that requires prompt treatment. Digital therapeutics (DTx) is an emerging field that employs remote monitoring and behavioural changes to manage diseases, with promising outcomes in ACS and post-percutaneous coronary intervention (PCI) patients. This study evaluates the efficacy of a software-driven DTx intervention in enhancing outcomes for CAD patients. Methods: This pilot, single-centred, prospective and real-world evidence cohort study aims to evaluate the effectiveness of a software-driven therapeutic intervention (LYFE) in patients with ACS and/or post-PCI. The study enrolled 30 patients over a 3-month follow-up period from October to November 2022. The main outcomes measured were changes in blood pressure, heart rate, medication adherence, the incidence of major adverse cardiovascular events (MACE), all-cause readmission, and lifestyle adherence at 1 and 3 months. Results: The mean age of the patients was 53.2±12.1 years; 27 (93%) males and 2 (7%) were females. Mean BMI of the patients was 26.3±5.0. The mean difference for systolic blood pressure (SBP) and diastolic blood pressure (DBP) was 7.8±10.9 (p=0.001*), 3.7±5.7 (p=0.002*) respectively with statistically significant reduction, at 3 months. The 25 (83.3%) patients had controlled blood pressure at 3 months. 27 (90%) patients were adherent to the medication and physically active, while 3 (10%) inactive throughout the study period. No CVD death/major bleeding event was reported. Conclusions: DTx improved medication adherence and blood pressure control in CAD, ACS with post-PCI patients during the study period.